2 - Universities and Regional Development: Lessons from the OECD Regional Assessment of the Free State, South Africa - Samuel Fongwa; Lochner Marais; Doreen Atkinson (Journal of Higher Education in Africa, 2014)
For the past few decades, the debate surrounding the ‘third mission’ of universities in South Africa has been dominated by the notion of univer- sity-community engagement. At the same time, the notion of regional development has come under the spotlight internationally. Drawing on existing literature on the relationship between universities, knowledge, the economy and community engagement, this paper scrutinises the OECD review of university-regional engagement in the Free State province in order to identify key lessons. Our contention is that, because the notion of regional engagement has become a central part of university manage- ment, assessment and even rankings, it should be viewed as an integral part of a university’s core activities of teaching and research, rather than as a separate third mission. Furthermore, findings reveal that a university’s engagement with its region also depends on regional assets and structures to support such processes.